PENGARUH STRATEGI PEMASARAN DALAM MENINGKATKAN KEPUASAN PELANGGAN : (Studi Kasus pada Perusahaan X di Surabaya) - Batseba Ester Marian (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2014)
Along with the development of global and local economic situation that is less favorable for the business world, then the companies today have to be innovative and creative in competing. Every company must have realized that marketing strategy plays an important role in the effort to survive and be able to make a profit in such situations. As was known, one of the goals of the company is to obtain the optimal profit, because profit will stimulate the growth of the company. Expected profit can be realized through the sale of goods or services. The aim of marketing is to meet consumer's needs and desires. Hence the marketing need to learn the desires, perceptions, preferences and behaviors of buyers as their targeted customers. Each organization / company of any kind to increase the sales volume must use marketing mix strategy, but the strategy of the marketing mix for real products and services are different This is related to differences in the characteristics of services and goods.